Nanoparticle-mediated delivery of herbal-derived natural products to modulate immunosenescence-induced drug resistance in cancer therapy: a comprehensive review - Yang, Lichang; Wu, Wei; Yang, Jing; Xu, Manman (Frontiers in Oncology, 2025)
Immunosenescence, the age-associated decline of the immune system, is pivotal in fostering drug resistance within the tumor microenvironment (TME). The accumulation of senescent immune cells and the release of pro-inflammatory senescence-associated secretory phenotype (SASP) factors create a milieu that supports tumor survival and undermines therapeutic efficacy. Traditional cancer treatments often fail to address this underlying issue, leading to suboptimal outcomes. This article proposes an innovative strategy to overcome immunosenescence-induced drug resistance through the nanoparticle-mediated delivery of herbal-derived natural products (HDNPs), which possess senolytic and immunomodulatory properties capable of clearing senescent cells and rejuvenating immune function. Nanoparticle delivery systems enhance these compounds’ stability, bioavailability, and targeted delivery to the TME and senescent immune cells. By harnessing the synergistic effects of HDNPs and nanotechnology, this approach offers a novel and multifaceted solution to drug resistance in cancer therapy. It holds the potential to restore immune surveillance, reduce pro-survival signaling in cancer cells, and enhance the efficacy of conventional treatments. This paradigm shift emphasizes the importance of addressing immunosenescence as a therapeutic target and paves the way for more effective and personalized cancer interventions.